Chapter A China fica ao lado / La Cina è accanto - Cavalletto, Silvia (Studi di Traduzione Letteraria Lusofona, 2022)
La Cina è accanto is the Italian translation of the equivalent Portuguese colletion of short stories A China fica ao lado. This literary work has been translated for the first time in Italian language by Silvia Cavalletto in this volume. The Italian translation provides the Italian reader to appreciate the language and the writing style of Maria Ondina Braga and to approach this relevant Portuguese author of the 20th century.